Seroprevalence of Leptospira infection in occupational risk groups in North Khorasan province, Iran. Issue 1 (January 2021) - Hashemi, Seyed-Ahmad; Arzamani, Kourosh; Abdollahpour, Gholamreza; Beheshti, Nazanin; Alavinia, Mohammad; Azimian, Amir; Neela, Vasantha Kumari; van Belkum, Alex; Ghasemzadeh-moghaddam, Hamed
Abstract: Leptospirosis is an important zoonotic bacterial disease caused by Leptospira spp. Earlier studies from North Khorasan province (Iran) reported the presence of Leptospira in wild canines and rodents. To date, there is no data on the seroprevalence of leptospirosis among humans in this province. This study was performed to determine the prevalence of human leptospiral infection among people with different occupations. The study was conducted in urban and rural areas of the province. Among the serum samples collected from 278 subjects, 3 (1.1%) showed positive reaction with titer of 1:100 by the microscopic agglutination test (MAT). Positive reactions were detected against Leptospira interrogans Canicola and L. interrogans icterohemorrhagic and all these samples were from livestock farmers (n = 3/106, 2.7%). The current study revealed that, though Leptospira infection is low in North Khorasan province, regular monitoring of the livestock and the farmers are important. Abstract : Leptospirosis; Microscopic agglutination test (MAT); livestock workers; North Khorasan province; Iran.